ABDOMINAL PAINS IN GIRLS ASSOCIATED WITH A GYNECOLOGICAL PATHOLOGY: FAILURES OF DIAGNOSIS AND TREATMENT - E. V. Sibirskaya; L. V. Adamyan; S. P. Yatsyk; S. G. Geras'kina (Union of pediatricians of Russia, 2014)
Abdominal pains are the most common manifestation of functional or organic pathology of the gastrointestinal tract; however, in girlsthey are often caused by various diseases of pelvic organs. The article presents the main nosological forms of gynecological diseases in female children and adolescents, the main symptom whereof is abdominal pains. The authors discuss methods of differential diagnosis and demonstrate that failures of diagnosis and management and treatment tactics are caused by insufficient knowledge of anatomy and physiology of the reproductive system, neglect of gynecological anamnesis, untimely diagnosis of apoplexies of ovaries and complicated functional cysts, lack of oncological suspicion when encountering tumors and tumor-like ovarian neoplasms.